Läsaren som medskaber av affekt. En paranoid och skamfylld läsning av Inger Christensens roman Azorno - Klara Meijer (The Royal Danish Library, 2015)
By changing the romantic ‘you’ into a paranoid ‘you’ in the beginning of the novel, Azorno changes the concept of romance- into a shameful and paranoid idea. The woman, in the first letter, who has been told to be ‘the only woman’ in the beginning of the novel, needs to guard her place and starts to feel anguish and hate around the four other women. This paranoia is contagious; it affects both form and reader. The changing of narrator and the fact that all narrators repeatedly are being accused by the next one of lying results in a feeling of not being able to distinguish true from false, fiction from reality in the reader. The shame, caused by the ambivalence; of not knowing – but wanting to know little by little makes the reader enjoy the feeling of being fooled. Thus makes it problematic for the reader to accept the traditional romantic ending of the novel. And a new type of seduction is desired.